2017
DOI: 10.2147/ott.s122992
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-320a inhibits tumor proliferation and invasion by targeting c-Myc in human hepatocellular carcinoma

Abstract: BackgroundDownregulated expression levels of microRNA-320a (miR-320a) were found in primary breast cancers and colorectal cancer. Previous findings indicated that miRNA-320a may involve in the cancer development. In this study, we explored the roles of miR-320a by targeting c-Myc in the tumor growth of hepatocellular carcinoma (HCC).MethodsQuantitative reverse-transcription polymerase chain reaction (qRT-PCR) was performed to detect the expression of miR-320a in 50 HCC tissues and four HCC cells. Luciferase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 40 publications
6
42
0
Order By: Relevance
“…The pathogenesis of CC is still not clear at present, though the infection of human papillomavirus (HPV) is correlated with CC; and HPV is not enough for promoting malignant transformation in the cervix, so other factors important for this process should be investigated (Dang, Zheng, Liu, Wu, & Wu, ; Liu, Liu, Guo, Liu, & Li, ). microRNAs (miRNAs) have been evinced to regulate tumor proliferation and invasion in cancers, and they are widely analyzed in diagnosis, therapies and prognosis of cancers (Kosaka, Iguchi, & Ochiya, ; Xie et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of CC is still not clear at present, though the infection of human papillomavirus (HPV) is correlated with CC; and HPV is not enough for promoting malignant transformation in the cervix, so other factors important for this process should be investigated (Dang, Zheng, Liu, Wu, & Wu, ; Liu, Liu, Guo, Liu, & Li, ). microRNAs (miRNAs) have been evinced to regulate tumor proliferation and invasion in cancers, and they are widely analyzed in diagnosis, therapies and prognosis of cancers (Kosaka, Iguchi, & Ochiya, ; Xie et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have also indicated that miRNAs may serve as oncogenes or tumor suppressors to regulate tumor cell proliferation, migration and invasion (11)(12)(13)(14). For instance, miRNA-320a inhibits tumor proliferation and invasion by targeting c-Myc in human hepatocellular carcinoma (15). Numerous miRNAs have been reported to regulate the progression of RB, including miR-29a (12), miR106b (13), miRNA-382 (16) and miRNA-320 (17); however, the functions of miRNAs in RB are yet to be determined and the roles of most miRNAs in RB remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…coding RNA molecules at length about 19 to 24 nucleotides, have established their value into multiple pathological processes, including cell proliferation, cell apoptosis and cell differentiation, through the post-transcriptional regulation of genes expression (6)(7)(8). Accumulating evidences disclose that several miRNAs act as important biomarkers for the diagnosis and prognosis of various cancers, such as NSCLC, pancreatic cancer and colorectal cancer (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%